STUDY OF PRECIPITATION AND LAND-USE IMPACT ON GROUNDWATER - SURFACE WATER INTERACTION AND GROUNDWATER QUALITY IN THE CIKAPUNDUNG WATERSHED - Nelson Tambunan, Ricky
The Cikapundung River is one of the important water resources for the city of Bandung and its surrounding areas. The Cikapundung River interacts with the surrounding groundwater system so that both affect each other, both in quantity and quality. Research on the interaction of groundwater and river water in the Cikapundung watershed and the quality of groundwater influenced by seasonal differences needs to be conducted, one of which can be a consideration for water resources management and flood disaster control. The measurement results in the short dry period, June - October 2023 showed that the transition zone from the effluent flow to the influent flow moved ± 1.7 km to the north towards the position of the research results in 2015. The measurement results in the short wet period, November 2023 - March 2024 showed that the transition zone from the effluent flow to the influent flow moved again by ± 1.2 km to the south towards its position in the short dry period of 2023. The runoff coefficient of the Cikapundung watershed using Cook's method was estimated at 70% where less than 30% of the precipitation is infiltrated into the subsurface, where the boundary of the area with the extreme runoff coefficient area is in the same area as the transition zone from effluent flow to influent flow in 2024. In contrast to the results of several studies elsewhere, the TDS concentration in groundwater is relatively higher in wet periods than in dry periods. The acidity of groundwater is relatively more acidic in the wet period than in the dry period.